DIGITAL LIBRARY APPLICATION POLYTECHNIC IMMIGRATION BASED WEBSITE - Priati Assiroj; w Wilonotomo; Akbariyatn Darma Putra (Polteknik Imigrasi, 2021)
Immigration Polytechnic Library is a knowledge resource for the academic community of Immigration Polytechnic. In carrying out the work process, the Immigration Polytechniclibrary uses a conventional librarysystem. Nevertheless, in its implementation, there are some shortcomings. Suchas the book’s physical condition that is easily damaged, the limited number of books with the same title, and the inhibition of members to borrow books directly due to the distance or due to covid-19 pandemic. This research aims to find out the Immigration Polytechnic Library business process current condition and give the illustration about the planningof Immigration Polytechnic Digital Libraryweb-based. This research needs to be carried out since it’s able to help solve the problem that occur in the work process of Immigration Polytechnic Library and as a contribution to Immigration Polytechnic by giving an innovation in the form of digital library application web-based. The design of the application uses the system development life cycle (SDLC) method. The result of this study is a prototype of a website-based digital library application that later can be applied and used by Immigration Polytechnic.